Pengaruh Tekanan Waktu, Materialitas Dan Risiko Audit Terhadap Pengentian Prematur Atas Prosedur Audit(Studi Empiris Pada Kantor Akuntan Publik Kota Semarang) - Mujiono, Rohmad Suryani (2016)
Pressure Effect of Time, Materiality, Audit Risk, Against Premature Termination Upon Procedures Audit. This study aims to determine the effect of time pressure, materilitas and audit risk to premature termination on audit procedures. The population in this study is the auditor who worked on Public Accounting Firm (KAP) Semarang is 18 Public Accounting Firm (KAP) and this study only took 7 Public Accounting Firm (KAP) of 18 Public Accounting Firm (KAP). While the sample of this research is the auditor who works in 7 Public Accounting Firm (KAP) in Semarang number of 47 respondents. The method of collecting samples by using a convenience sampling technique. In this study to analyze the data was performed using multiple linear regression analysis. The results showed that significantly influence the time pressures of premature pengentian on audit procedures, materiliatas significant effect on premature termination on auditing procedures and audit risk significant effect on premature termination on audit procedures.